Post-game recovery of isometric hamstring strength in a high-risk hamstring strain injury group throughout an Australian Football League season - Sutherland, T; Heasman, J.; Rogalski, B.; Fahey-Gilmour, J.; Peeling, P. (Science and Medicine in Football, 2024)
This study sought to investigate post-game hamstring strength recovery of 26 Australian Football League (AFL) players with a previous hamstring strain injury (HSI) across an AFL season. Maximal unilateral isometric knee flexion strength was assessed using an externally fixed dynamometer, and inter-session reliability was measured during the pre-season period. Linear mixed effects models investigated the influence of numerous variables on post-game hamstring strength decrement (relative change between initial weekly test and individual baseline) and individual within-week strength change following gameplay. The test demonstrated good inter-tester reliability (ICC = 0.81-0.88; CV = 6.73-7.33), and an acceptable level of error (MAE = 5.77-7.14%). Player as a random effect strongly influenced post-game strength decrement and within-week strength change (marginal R2 = 0.185-0.407; conditional R2 = 0.455-0.654). Within-week hamstring strength change was strongly determined by post-game strength decrement alone (estimate = 0.51, 95% CI = -0.66- -0.36 ; ?2 = 0.32; P=<0.001) and in interaction with number of days post-game (estimate = 0.43, 95% CI = 0.20-0.66; ?2 = 0.096; P=<0.001). This study shows the importance of early individual assessment of post-game hamstring strength in players with prior hamstring injury and could be valuable to inform post-game hamstring recovery in future applications.